Using interactive web training to teach parents to select function-based interventions for challenging behaviour: A preliminary study. Issue 4 (2nd October 2019) - Marleau, Brigitte; Lanovaz, Marc J.; Gendron, Alexie; Higbee, Thomas S.; Morin, Diane
ABSTRACT: Background: Children with a developmental disability often engage in challenging behaviour, which may require that parents implement behavioural assessments and interventions. The purpose of our pilot study was to examine the effects of an interactive web training (IWT) to teach behavioural function identification and intervention selection to parents. Method: Twenty-six parents of children with a developmental disability responded to function identification and intervention selection tasks on clinical vignettes before and following IWT. We also measured social validity and the duration of training. Results: Our results show that parents were more accurate in the identification of behavioural function and selected more adequate interventions following IWT. On average, parents spent less than 2.5 h to complete IWT and rated it positively. Conclusions: The IWT appears to be a viable tool to teach parents about function-based intervention, but additional research is needed to examine whether it translates to changes in parental practices and child behaviour.